One fine day - Obst, Lynda Rosen; Seltzer, Terrel; Simon, Ellen; Hoffman, Michael, 1956-; Pfeiffer, Michelle, 1957-; Clooney, George; Stapleton, Oliver; Fox 2000 Pictures; Via Rosa Films; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, CA : Twentieth Century Fox Home Entertainment, 2006)
Two single parents are inadvertently thrown together for one chaotic day -- and love, of course, blooms.
Originally released as a motion picture in 1996.
Widescreen format, interactive menus, scene selection, original theatrical trailer.
Michelle Pfeiffer, George Clooney.
DVD, Dolby surround, widescreen letterbox format.
Keywords: Single parents; Man-woman relationships; Feature films; Comedy films; Films for the hearing impaired